The Price of Survival. On the Ontology of Animals in Transcaucasia, using the Example of Georgia (London Journal of Research In Humanities and Social Sciences, 2025)
This academic essay titled The Price of Survival. On the Ontology of Animals in Transcaucasia, Using the Example of Georgia was developed in the wake of a professional trip to an international congress held inTbilisi, the capital of Georgia, in October 2024.At its core, the study analyzes snapshots of a human-pet constellation which, in Georgia, has given rise to a daily culture of indifference. This culture reflects fundamental ontological questions about coexistence, polemically mirroring the ethical and moral categories between human existence and the status of the animal as a thing.The empirical dimension of the paper is illustrated through numerous encounters with suffering animals in Georgian urban spaces. These observations illustrate the cruel living conditions under which pets are forced to existwithout societal recognition and in the absence of institutional animal welfare structures.In addition, the findings are placed within a historical framework, discussing and interpreting human-animal relationships ranging from antiquity to the 21st century.
Keywords: curriculum development; Constructivism; Philippine Education; student-centered; Lacking animal protection in Georgia; animal ethics as a moral deficit in the 21st century; cultural indifference in the Transcaucasus; lack of awareness